A woman’s engagement and entitlement to the dowry in the Holy Qur’an, an analytical study (Journal of the College of Basic Education, 2026)
Islamic law permits a man during the waiting period to hint at proposing marriage to a woman whose husband has died or divorced her irrevocably. Proposing marriage to a woman during her waiting period is explicitly prohibited, and concluding a marriage contract with her before the end of her waiting period is absolutely prohibited, out of respect for marital rights Islam has not neglected any aspect of married life. Rather, it has set specific legal rulings for it, whether in terms of understanding and affection, or estrangement and estrangement. Such rulings include a man praising himself and mentioning his good deeds to hint at marriage, or giving a woman a gift during her waiting period without a secret appointment. It is not permissible to contract a marriage with a woman during her waiting period under any circumstances. Rather, it is permissible after the waiting period has ended. People should be mindful of Allah, fear Him, and fear His punishment. As for a woman for whom a dowry was specified in the marriage contract, and she was divorced before consummation, she is entitled to half of the dowry, which she takes without restriction, unless the divorced woman forgives it and waives her right, or her guardian who holds the marriage contract forgives her. Forgiveness is closer to piety, and the man and woman should be compassionate toward each other. This research attempts to uncover some of the views of some commentators and jurists regarding the verses that discuss the ruling on proposing marriage to a woman during the waiting period following death or divorce, and the ruling on a woman who has been divorced before consummation.